Correlation Between Students’ Attitudes and Mathematics Learning Achievements of High School Students in Yobe, Nigeria - Musa, Saleh; Mamudo, Wasilatu Saleh; Mohammed, Babagana Butu; Audu, James Hirhyel (Indonesian Journal of Science and Mathematics Education, 2022)
Attitudes can affect the overall behavior of students in the learning process. This study aims to investigate the correlation between students’ attitudes and mathematics learning achievements among 367 senior secondary school students in Yobe state, Nigeria. A correlational design was used in the study. The research instruments used were questionnaires designed by the researchers to elicit responses from the students and end-of-term 3rd term mathematics examination scores of the students. The respondents were measured with a relevant standardized scale with Cronbach alpha reliability of 0.83. The data obtained was analyzed using Pearson Product Moment Correlation and t-test for independent sample. The result showed that there was a significant correlation between students’ attitudes and mathematics learning achievements of high school students’. In addition, there was a significant difference between male and female students’ attitudes toward mathematics learning achievements of high school students. Thus, it can be concluded that students' attitudes and learning achievement in mathematics are positively related. Female students are more prone to math phobia. In view of these findings, it is recommended that teachers should be wary of student attitudes toward learning mathematics and ensure that mathematics phobias are drastically minimized.